A new spin crossover FeII coordination environment in a two-fold interpenetrated 3-D Hofmann-type framework material. Issue 1 (27th November 2020) - Ahmed, Manan; Xie, Zixi; Thoonen, Shannon; Hua, Carol; Kepert, Cameron J.; Price, Jason R.; Neville, Suzanne M.
Abstract : Spin-crossover is observed for the first time in a Fe II (py)3 (NC⋯)3 coordination environment which arises in a two-fold interpenetrated 3-D Hofmann-like framework. Abstract : A 3-D Fe II Hofmann-type framework material has been prepared which contains a three-connecting pyridyl-donor ligand with amide functionality and [Au(CN)2 ] − metallo-ligands. The Fe II sites display a rare Fe II (py)3 (NC⋯)3 coordination environment, which we show for the first time to be conducive to spin crossover (SCO).